Analysis of the Arrangement and Distribution of PJOK Teachers in Tarutung District North Tapanuli Regency - Aritonang, Lora; Imran Akhmad; Ibrahim , Ibrahim (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2024)
The aim of this research is to look at the analysis of the arrangement and distribution of PJOK teachers in Tarutung District, Deli Serdang Regency. The method used in this research, the approach that will be used is a qualitative research approach with descriptive methods. The results of the research on the structuring aspect with a total of 4 lesson hours (JP) with a time of 1 JP 35 minutes, the total PJOK lesson hours for District Elementary Schools in Tapanuli Regency amounted to 9.640 hours. There are 140 PJOK teachers in 15 sub-districts in North Tapanuli Regency. The aspect of mapping the need for PJOK teachers is 43 people, while currently Tarutung sub-district only has 15 teachers, meaning there is a shortage of 28 PJOK teachers in Tarutung sub-district that must be resolved. The conclusion in this research is that there are 140 PJOK teachers while the need for PJOK teachers is 402 teachers, so the shortage reaches 70%.